IDENTIFIKASI RISIKO BIAYA PELAKSANAAN PROYEK KONSTRUKSI GEDUNG BAGI PERUSAHAAN KONTRAKTOR - Alfa Taras Bulba; Anita Rauzana; Ikhlas Kurniawan (Universitas Teuku Umar, 2022)
One aspect that is needed in the implementation of infrastructure development is the availability of funds or capital from the government. Budget proposals from local governments are sometimes not the same as those approved by the legislature. area. The approved budget sometimes does not match the value of the Engineering Estimate work that has been generated from the DED planning. So this affects the execution of the work. There are several conditions that directly affect cost overruns in the implementation of building construction work. Some of these conditions include inadequate worker qualifications, procurement of materials that are sometimes not in accordance with the implementation time, natural conditions that sometimes delay the completion of work or natural disasters such as floods, inappropriate implementation methods, implementing management who do not understand the implementation conditions as well as several other conditions. In connection with these problems, this study wants to analyze the dominant risk factors that affect the cost of implementing building construction projects in Aceh Province. This research is a quantitative research. Based on this research, the dominant factor influencing the cost of implementing building construction projects in Aceh is force majeure with a mean value of 4.353.